COVID-19: Clinical aspects and therapeutics responses (2020)
COVID-19 has created havoc in the world by causing thousands of demises in a short period of time. Up till now, several attempts have been made for potential therapeutics against SARS-COV2. In this retrospective, single-center study, we extracted data from 122 COVID-19, RT-PCR confirmed patients. who were treated with a new treatment strategy of lianhuaqingwen with Arbidol Hydrochloride. The patients were either asymptomatic or had mild symptoms for COVID-19 disease. Of 122 patients 21 (17.21%) patients developed severe conditions of COVID-19, while total 111 (90.9%) experienced mild symptoms such as fever in 93 (76.22%) patients, cough in 23 (20.17%) and muscle pain were observed in total 8 (7%) patients. Furthermore our newly applied drugs combination (Lianhuaqingwen and Arbidol Hydrochloride) showed therapeutic effects in 5–7 days in patients with mild symptoms with 98% recovery rate. These results indicate that COVID-19 patients with mild symptoms can be treated with Lianhuaqingwen and Arbidol Hydrochloride. However, extensive clinical investigations are required to confirm the effectiveness of these drugs.